Growing the footprint of traditional grain origination - Ploeger, Dustin (Kansas State University, 2010)
This thesis focuses on the rapid growth of new generation contracts used by grain producers. Specifically, the research studies a potential customer base of producers not using Cargill’s new generation contracts. A survey was conducted to uncover possible customer demand for Cargill’s marketing solutions. Those surveyed do not have the opportunity to use these solutions because their operations typically lay outside the footprint of existing Cargill grain facilities. With Cargill’s Flex Delivery Program, sales professionals have the ability to sell grain marketing solutions, like new generation contracts, to farming operations outside of existing asset footprints. From the experiences of current sales professionals offering new generation contracts via Cargill’s Flex Delivery Program, the author hypothesized that there are three primary variables influencing the likelihood of a customer finding value in the Flex Delivery Program. The size of farming operation, the number of facilities they deliver grain to and the importance they place on forward marketing are critical components to determining if a farming operation may market grain through Cargill’s Flex Delivery Program using a new generation contract. The survey results revealed the percentage of the sample population fit the criteria of a Flex Delivery candidate. The survey questions were also designed to uncover farmer demographics, current marketing styles, competition, and, in general, provide good background information useful for making follow-up sales calls on those selected to survey. The results show roughly a third of those surveyed are Flex Delivery candidates.
Keywords: Risk Management; Contract; Futures; Grain; Agriculture, General (0473); Business Administration, Marketing (0338); Economics, Agricultural (0503)